Terrain Characterizations and Classifications of Semanggol Formation and Its Adjacent Areas by Using Remote Sensing and GIS Techniques - Muhammad Hasni, Danial Ilman (2016)
Semanggol formation is a geological formation existed in the northern part of Peninsular Malaysia. Semanggol formation is mainly divided into three main sections due to several factors including tectonism. The existence of a major strike-slip fault of (Bok Bak fault) is believed to be the main contributor of the division of Semanggol formation especially in central and north Kedah. Despite of extensive researches have been conducted to prove the occurrence of this fault in relation to Semanggol formation, none of them focuses on the aerial interpretation in studying the formation in a wider scale. This has been one of the factors of why this study is being conducted. By using a cutting-edge technology of remote sensing and Geographic Information System (GIS), this study will focus on finding the evidences related to the fault formation while giving thorough evaluation of terrain analysis that coexisted in the area. This study is completed with the assistance of satellite images as well as few software to clarify the observation within the region of study.